2021
DOI: 10.1016/j.eucr.2021.101671
|View full text |Cite
|
Sign up to set email alerts
|

Foreskin necrosis – Complication following self-circumcision

Abstract: Male circumcision (MC) seems to be practiced since ancient times by Muslims and Jewish, and it is considered as commandment. Attempts at self-circumcision for any reason are very rare in our country. This article aims to highlight another case of self-circumcision in a 30 year-old male, using a sharp vegetable knife. The reasons behind this act are various and the most common complications, especially in the use of sharp tools, in addition to bleeding or laceration of the penis, are infection, penile curvature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For example, this phenomenon may induce an increase in selfcircumcision practice, an emerging phenomenon [24,25]. In this context, misleading information may lead to a higher risk of complications, such as foreskin necrosis [26]. Secondly, we discovered that out of 60 videos, 75% were produced in India, a country with a high impact of penile cancer (incidence rate of up to 3.32 per 100,000 men in some regions) [27].…”
Section: Discussionmentioning
confidence: 88%
“…For example, this phenomenon may induce an increase in selfcircumcision practice, an emerging phenomenon [24,25]. In this context, misleading information may lead to a higher risk of complications, such as foreskin necrosis [26]. Secondly, we discovered that out of 60 videos, 75% were produced in India, a country with a high impact of penile cancer (incidence rate of up to 3.32 per 100,000 men in some regions) [27].…”
Section: Discussionmentioning
confidence: 88%
“…Of course, this requires more data to illustrate. Post-operative wound infection is a common complication after circumcision 25 , and post-circumcision wound infection may lead to occlusion of hair follicles or obstruction of exocrine ducts 22 , thereby increasing the occurrence of secondary epidermoid cysts of the penis. In this study, we did find that in patients with postoperative infection, the appearance of secondary epidermoid cysts of the penis was earlier (Tables 6 and 7 ), so the prevention of infection after circumcision is very important.Phimosis is one of the indications for circumcision, and it has been reported that secondary epidermoid cysts of the penis occurred in patients after phimosis 23 .…”
Section: Resultsmentioning
confidence: 99%
“…13 Due to inadequate expertise or lack of proper equipment, accidental cuts or injuries can occur during circumcision procedures. 14 These injuries may range from minor lacerations to more severe damage such as partial amputation of the glans or shaft of the penis. Such traumatic incidents not only cause immediate physical harm but also have long-term psychological consequences for individuals affected.…”
Section: High Prevalence Of Complications In Male Circumcisionmentioning
confidence: 99%